Avatar, Tar Sands, and Dad. Issue 2 (May 2018) - Sutton, Timothy
This is an (auto)ethnographic performance inspired by a conversation with my father while leaving the theater after watching Avatar back in 2009. It is intended to be performed as readers' theater. In it, I examine the role anthropology plays in the performance of imperialist nostalgia across the stories of James Cameron's film Avatar, Ursula K. Le Guin's novella The Word for World Is Forest, and Theodora Kroeber's Ishi in Two Worlds: A Biography of the Last Wild Indian in North America . I see a performance of alternative possibilities in Le Guin's utopian speculative fiction and in recent Indigenous-led activism opposing megaresource extraction projects such as Alberta's tar sands and the pipelines that snake out from it.